Research and Analysis of Ball Sports Learning in Inspiring and Aiding Students’ Diversification Education - Rui Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
With the development of university education, the number of students’ enrolled in colleges is increasing; as a result, the scale of college students' training is also gradually expanding, exposing the contradiction between the quality and quantity of college students' training. With the development of the social economy, individuals tend to pay more attention to their health. Ball sports are viewed as a sport that combines entertainment, viewing, and fitness, which require a relatively lower level of equipment and personal skills. Adapting to the dynamic changes developing in society in this information age is in line with the modern educational concept. Its use in badminton teaching and learning is in line with the students' own developmental needs and stimulates the students' potential. While exercise promotes the development of students in many aspects, and lays down a solid foundation for students' learning and development. The educational value of class teaching is in secondary vocational schools. This paper puts forward a research-based analysis of ball sports in inspiring and aiding students' diversification education. It is necessary to coordinate the development quality of college students with the development of scale and quantity. In the process of teaching, we must break through the limitations of the traditional teaching mode and attach importance to the multi-teaching mode. Diversification education promotes the ability of students to innovate and the educational value of ball teaching in colleges and universities.